Tailored P2/O3 phase-dependent electrochemical behavior of Mn-based cathode for sodium-ion batteries. (1st August 2023) - Saxena, Samriddhi; Vasavan, Hari Narayanan; Badole, Manish; Das, Asish Kumar; Deswal, Sonia; Kumar, Pradeep; Kumar, Sunil
Abstract: The development of mixed structures is increasingly becoming an efficient way to improve the performance of layered oxide cathodes for sodium-ion batteries. Herein, the Na0.8 Mn0.6 Ni0.3 Cu0.1 O2 (NMNC) cathodes with varying fractions of P2/O3-type phases are prepared by adjusting the calcination conditions. The Rietveld refinement of X-ray diffraction (XRD) data confirms the increase in O3 phase fraction from 7 % to 27 % with the increase in calcination temperature from 850 °C to 950 °C. The sample prepared at 850 °C (NMNC-850) exhibits the highest specific capacity (139 mAh g −1, 100 mAh g −1, and 80 mAh g −1 at 0.1C, 1C, and 4C, respectively) and best rate performance among all samples in addition to an excellent cyclability with capacity retention of ~85 % after 100 cycles in 1.5–4.2 V range. The increase in the O3 phase fraction leads to a drastic degradation of rate performance. The galvanostatic intermittent titration technique confirms a diffusion coefficient of 5.13 × 10 −13 –5.25 × 10 −10  cm 2  s −1 in biphasic NMNC-850 sample. Ex-situ XRD studies confirm a reversible P2/O3 → P2/P3 → P2/O3 transformation in NNMC-850 during cycling. The improved electrochemical performance is attributed to the presence of non-identical neighboring phases in suppressing the phase transformations during cycling. Graphical abstract: Unlabelled Image Highlights: Tailored P2/O3 Na0.8 Mn0.6 Ni0.3 Cu0.1 O2 (NMNC) materials by varying calcination temperature A capacity of 139 mAh/g and excellent rate performance in NMNC-850 NNMC-850 transforms reversibly as P2/O3 → P2/P3 → P2/O3 during cycling. Improved cyclability in the 1.5–4.2 V range